2017
DOI: 10.1021/acs.jpcc.7b07598
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Photophysical Properties with the Photoacoustic Emission for a Selection of Established Chromophores

Abstract: An archetypal study is presented to correlate both the optical and the photoacoustic (PA) properties for a diverse selection of dyes whose structural properties range across organic and inorganic, symmetric and asymmetric, and neutral and cationic systems. Three distinct classes of molecular PA contrast agents have been identified and classified according to their optical-PA response as either (i) linear absorbers linear PA emitter, (ii) saturable absorbers weak PA emitter, or (iii) reverse saturable absorbers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
46
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(46 citation statements)
references
References 61 publications
(82 reference statements)
0
46
0
Order By: Relevance
“…This is consistent with the weak PA emission observed for the same dyes across a wider range of laser fluences. As anticipated, the reference CV dye maintains a linear optical absorption at all laser fluences consistent with its steady PA emission, which can be used as a baseline to identify nonlinear PA emission in other dyes . For example, the natural curcumin derivative 1 and DMA‐2 exhibit a modest reverse saturable absorption response comparable to the reference cyanine dye Cy5, all of which exhibit an enhanced nonlinear PA emission relative to the CV linear reference.…”
Section: Resultsmentioning
confidence: 65%
See 2 more Smart Citations
“…This is consistent with the weak PA emission observed for the same dyes across a wider range of laser fluences. As anticipated, the reference CV dye maintains a linear optical absorption at all laser fluences consistent with its steady PA emission, which can be used as a baseline to identify nonlinear PA emission in other dyes . For example, the natural curcumin derivative 1 and DMA‐2 exhibit a modest reverse saturable absorption response comparable to the reference cyanine dye Cy5, all of which exhibit an enhanced nonlinear PA emission relative to the CV linear reference.…”
Section: Resultsmentioning
confidence: 65%
“…For nonlinear absorption processes, which typically requires a high laser fluence and of course a resonant excited state absorption, a PA signal enhancement is generated by a quadratic dependence on Ι In a prior study we demonstrated that the naphthyl substituted curcumin 4 exhibits the most impressive reverse saturable absorption and nonlinear PA emission of any curcumin dye studied to date . In this study, the optical and photoacoustic responses for compounds 1 , 3 – 5 , DMA‐2 – DMA‐5 and reference dyes crystal violet (CV), Cy3 and Cy5 have been evaluated using the photoacoustic z‐scan (PAZ) method using 532 nm laser irradiation in acetonitrile. For in vivo PA imaging applications it is preferred to employ water‐soluble chromophores with a strong absorption in the biological window (680–980 nm).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Except for cells containing melanin, PA contrast is usually undetectable in biomaterials and the cell-laden 3D culture, and so an exogenous contrast agent needs to be introduced for contrast enhancement. Exogenous contrast agents for use in PA molecular imaging have to possess certain photophysical and biological properties, such as efficient optical-to-PA conversion, long-lived excited-state lifetime, biocompatibility, distinct optical absorption spectra (where the endogenous contrast agents have a lower absorption), and the capability to pass through cellular and fibrillar barriers for successful labeling [29,36]. Furthermore, both endogenous and exogenous contrast agents are usually with optical absorption spectra in the nearinfrared (NIR) window (600-1100 nm) so as to ensure their deeper penetration and hence the required imaging depth.…”
Section: Photoacoustic Microscopymentioning
confidence: 99%
“…The use of fluorescent probes for photoacoustic imaging seems far from efficient because fluorescent dyes will waste a fraction of their excited-state energy by emitting a photon. Hatamimoslehabadi et al have compared the photophysical properties with the photoacoustic response for a selection of established chromophores, revealing the importance of a large non-radiative/radiative decay rate constant ratio for a good photoacoustic performance [ 33 ]. For example, fluorescein is a highly emissive dye with poor photoacoustic properties, while phenolphthalein, a fluorescein derivative, is non-fluorescent yet shows good photoacoustic properties [ 34 ].…”
Section: Introductionmentioning
confidence: 99%